Comoros : Staff Report for the 2001 Article IV Consultation and Discussions on a Staff-Monitored Program. (IMF Staff Country Reports; Country Report, 2001)
The federal government has made progress in reducing fiscal imbalances and improving public services. The authorities sharply reduced expenditures on goods and services and transfers, and improved management of the payroll generated a 5 percent reduction in the wage bill compared with 1999. Executive Directors welcomed the staff-monitored program (SMP)'s emphasis on improving fiscal sustainability, and they strongly supported a continuation of the tight public sector wage policy, and endorsed the authorities' plans to reduce employment in the public sector as part of a civil service reform program.